Penyuluhan Keluarga Sakinah Pada Lansia Di Desa Sana Daja Pasen Pamekasan - S. Fathiyatul Jannah; Kamilatul Mukarromah; Subhanallah Subhanallah Muchtar (STAI Publisistik Thawalib Jakarta, 2023)
The aim of the study was to identify and describe the Sakinah family members in the elderly in Sana Daja Village, Pasean, Pamekasan. The research was conducted qualitatively through case studies. Data collection techniques: interviews with 1 extension worker, 2 extension assistants, and 3 elderly couples. Data processing techniques with reduction, presentation, and conclusion. Data validation technique with technique and source triangulation. The results showed: (1) the implementation of counseling: first, the preparation of counseling, namely influencing the place of counseling is Pasean Pamekasan Religious Affairs Office and preparing counseling materials including self-introspection material, hiding religious values, exemplary, harmony, Qana'ah, and the rights and obligations of husband and wife. The second implementation of counseling: is carried out face to face with the opening stage, giving materials, and closing. 2) The impact of counseling: adding insight about building a sakinah family for the elderly and the community feeling spiritual cleansing.